Peacebuilding in Colombia: without women, there can be no peace - Garrido Ortolá, Anabel (Cuadernos de Gobierno y Administración Pública, 2021)
Women's political participation in peace negotiations in different countries has been marked by a history of absence. For this reason, the United Nations Council passed Resolution 1325 (2000), which urges countries to include women's participation at peace negotiation tables. The Sustainable Development Goals (SDGs) follow in this wake by including peace, justice, strong institutions and achieving gender equality and empowering all women and girls among their development goals. In this vein, this article addresses women's participation in peace negotiations in Colombia: from the first negotiations in the 1990s to the latest agreement between the government and the FARC-EP (2016). This will make it possible to assess how public peacebuilding policies are being carried out from a gender perspective. Equitable implementation is essential, because it is clear from the lessons learned that only with them will peacebuilding be possible in Colombia.
Keywords: Colombia; gender; women; conflict; security; peace processes